THE CHOICE OF THE PERSONAL DIARY AS A FORM OF LITERARY WRITING IN LOS DETECTIVES SALVAJES BY ROBERTO BOLAÑO - Acevedo Zapata, Luis Alejandro (2022)
A significant part of the studies focused on the novel by Roberto Bolaño (1953-2003), Los detectives salvajes, focuses its attention above all on the main characters of the novel: Arturo Belano and Ulises Lima, literary transfiguration of the author himself and of the Mexican poet Mario Santiago Papasquiaro, according to the criticism on the matter. However, the narrator of two thirds of the novel is Juan García Madero, a young 17-year-old poet who is the one who narrates in his personal diary the adventures lived alongside those who he considers his life teachers and who initiate him on the path of poetry by making him part of a group of poets with similar sensibilities. This article intends to review the importance of this character for the articulation of the plot and the novelistic fiction that autobiography and autofiction entails.